Systemic therapy‐based split‐course stereotactic body radiation therapy. Issue Volume 6:Issues 4(2022) (27th November 2022) - Zheng, Rong; Wang, Bisi; Liang, Feihong; Xu, Benhua
Abstract: Purpose: Given the therapeutic toxicity of concurrent chemoradiotherapy, the dose of chemotherapy is always limited. Hence, the question of how to administer adequate chemotherapy to synchronize stereotactic body radiation therapy (SBRT) treatment strategy for maximizing the benefits of neoadjuvant therapy to improve prognosis is a challenging and debatable issue. Methods: We summarized the major clinical trials and preclinical studies of split‐course CRT and split‐course SBRT and explored the feasibility and theoretical advantages of implementing split‐course SBRT and systemic therapy simultaneously. Results: Split‐course radiotherapy is a strategy mainly proposed with the aim of further reducing the toxicity of radiotherapy and improving the patient's treatment tolerance, with added features of the extended interval between the fractions instead of daily irradiation. In the past, split‐course radiotherapy was not a recommended treatment strategy in terms of local tumor control rates, late response rates, and survival without significant improvement relative to continuous radiotherapy. Split‐course SBRT has different biological effects compared to split‐course conventional radiotherapy (CRT). The current findings suggest that the split‐course SBRT model has good treatment tolerance and facilitates the implementation of adaptive radiotherapy. Conclusion: This treatment strategy facilitates the upgrading of radiotherapy doses and the combination with systemic therapy, especially with vascular targeting agents and immunotherapy, thus avoiding the disadvantages of split‐course CRT, such as reduced local control rate, increased treatment time and economic cost, and has the potential to achieve better tumor suppression. Abstract :